Synergy of Teachers and Parents in Dealing with the Challenges of Speech Delay in Children Aged 3–4 Years - Debby Adelita Febrianti Purnamasari (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
Speech delay is one of the language development problems that is quite often found in early childhood. This condition can affect communication skills, social interaction, and children's readiness to enter the next level of education if not handled appropriately. This study aims to analyze the form of synergy between teachers and parents in dealing with speech delay in children aged 3–4 years. The research uses a qualitative approach with a case study method. Data was obtained through observation, in-depth interviews with teachers and parents, and documentation of child development. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the success of handling speech delay is influenced by intensive communication between teachers and parents, consistency in providing language stimulation at school and at home, the use of educational media, and collaboration with professionals when needed. The main obstacles include limited parental time, low understanding of speech delay, and excessive use of gadgets. This study confirms that planned, sustainable, and child-based collaboration is able to improve the development of language skills optimally.